1954
DOI: 10.1128/jb.67.6.640-650.1954
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Bacteriophage T5 and Its Intracellular Growth—a Study by Complement Fixation

Abstract: Infection of a susceptible bacterium by a virulent phage particle is followed, after a latent period, by cell lysis and liberation of newly formed phage particles. The infecting particle loses its infectivity shortly after adsorption to the host, a fact attributed to disociation of the particle into a-cell penetrating fraction, consting chiefly of nucleic acid, and an externally persisting fraction, consisting chiefly of protein and containing at least some of the principal phage antigens (Hershey and Chase, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1954
1954
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Preliminary experiments confirmed several of the results of Adams (1949), Kay (1952), and Lanni (1954). The following points were established:…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Preliminary experiments confirmed several of the results of Adams (1949), Kay (1952), and Lanni (1954). The following points were established:…”
Section: Resultssupporting
confidence: 74%
“…(5) Plating of T5 infected bacteria by the agar layer method directly from chilled samples often causes an important loss of infective centers. This was probably responsible for the loss of infected bacteria that complicated some of the experiments by Lanni (1954). We found that this loss can be avoided if the samples are warmed for several minutes at 37 C before being plated.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The host range analysis indicates that PR1 successfully infects most P. rettgeri strains used in this study, with a high efficiency of plating (EOP), while not being able to lyse certain other closely related bacteria of the tribe Proteeae and the Enterobacteriaceae family, such as P. stuartii, P. alcalifaciens, Citrobacter freundii, Morganella morganii, P. mirabilis, or Proteus vulgaris (Table 1). Compared to other characterized phages of T5virus genus (T5 and AKFV33), PR1 presents a short latent period of 25 min and burst size of 32 (23,26).PR1 genomic features. The PR1 virion contains a linear 118,537-bp doublestranded DNA (dsDNA) molecule ( Fig.…”
mentioning
confidence: 89%